Effects of Cu addition on microstructure and mechanical properties of as-cast Mg-6Zn magnesium alloy - Yu Zhang (China Foundry, 2017)
The application of Mg-Zn binary alloys is restricted due to their developed dendritic microstructure and poor mechanical properties. In this study, an alloying method was used to improve the mechanical properties of Mg-Zn alloy. The Mg-6Zn magnesium alloys microalloyed with varying Cu content (0, 0.8, 1.5, 2.0 and 2.5wt.%) were fabricated by permanent mould casting, and the effects of Cu content on the microstructure and mechanical properties of as-cast Mg-6Zn alloys were studied using OM, SEM, XRD and tensile tests at room temperature. The obtained results show that the addition of Cu not only can refine the grains effectively, but also can modify the eutectic morphology and improve the mechanical properties of the alloys. The main phases of the studied alloys include α-Mg, MgZn2, Mg2Cu and CuMgZn. When the content of Cu exceeds 0.8wt.%, Mg2Cu phase appears. Meanwhile, the eutectic morphology is modified into dendritic shape or lamellar structure, which has an adverse effect on the tensile properties. Furthermore, among the investigated alloys, the alloy containing 0.8% Cu shows an optimal ultimate tensile strength of 196 MPa, while the alloy with 1.5wt.% Cu obtains an excellent elongation of 7.22%. The experimental alloys under different Cu contents show distinguishing fracture behaviors: the fracture of the alloy with 0.8wt.% Cu reveals a mixed mode of inter-granular and quasi-cleavage, while in other investigated alloys, the fracture behaviors are dominated by cleavage fracture.